Agropastoral activities increase fluctuating asymmetry in tadpoles of two neotropical anuran species. (22nd June 2017) - Costa, Renan N.; Solé, Mirco; Nomura, Fausto
Abstract: Agriculture and pasture activities are the main drivers for habitat reduction, directly affecting amphibian assemblages. In the Cerrado, the progress of agricultural and pasture areas negatively affects aquatic environments and their organisms, once the suppression of marginal vegetation reduces the natural protection against allochtone stressors. One possible way to measure the stress level is the Fluctuating Asymmetry (FA), which is calculated based on the deviations in the development of bilateral morphological traits of the organism. Herein, we evaluated whether environments with a higher degree of agropastoral influence and reduced marginal vegetation can increase FA levels in tadpoles of two common and widely distributed anuran species in the Cerrado ( Physalaemus cuvieri and Scinax fuscomarginatus ). We sampled and classified water bodies according to the percentage of agropastoral land use and marginal vegetation, and measured four morphological traits of tadpoles to evaluate the degree of FA. We found that in environments with intensive agropastoral land use, tadpoles of P. cuvieri and S. fuscomarginatus had higher FA in nostril‐snout distance (NSD). In environments with reduced marginal vegetation, tadpoles of S. fuscomarginatus had higher FA in eye width (EW), but no effect was detected for tadpoles of P. cuvieri . These morphological traits (i.e. nostrils and eyes) are associated to individual fitness of tadpoles. Thus, these developmental deviations can affect species fitness and population homeostasis over time, contributing to generate stochastic population dynamics and increasing the vulnerability of native species to local extinctions. The use of FA as a tool to measure environmental impact on species with potential to be used as bioindicators can contribute to generate and test hypothesis when integrated with long‐term studies.